RELIGIOSITY, FAMILY GENDER ROLES SOCIALIZATION, AND COLLEGE STUDENTS’ ATTITUDES TOWARDS LESBIAN, GAY, BISEXUAL, AND TRANSGENDER (LGBT) - Izdihari Nisa’ul Husna; Diah Krisnatuti; Musthofa (Journal of Child, Family, and Consumer Studies, 2022)
Society’s attitudes towards LGBT can be understood through college students’ viewpoints as the university’s environment can act as a microcosm of a larger community. Their voices can act as a representation of the youth generation and fellow citizens’ tolerance. This study aims to analyze the influences of religiosity and family gender roles socialization on students’ attitudes toward LGBT. Primary data used in this study were collected through an online questionnaire filled by 60 respondents, divided into male and female, who were selected by multistage random sampling technique involving all IPB’s undergraduate programs. This study found a significant difference between male and female students’ rejection of lesbians, with female students having higher rejection than male students. Students' religiosity and family gender roles socialization are in the medium category. Sex positively correlated to attitudes toward lesbians, while the mother's Occupation positively correlated to family gender roles, socialization, and religiosity was found to positively correlate with attitudes toward lesbians, gays, bisexuals, and transgender. Sex, explicitly being female, positively influences attitudes toward lesbians. In contrast, religiosity positively influences attitudes toward lesbian, gay, bisexual, and transgender, which means female students have a higher rejection of lesbians. The greater religiosity will result in increased rejection of LGBT.